Drosophila soluble guanylyl cyclase mutants exhibit increased foraging locomotion: behavioral and genomic investigations. - Riedl, C.A.; Neal, S.J.; Robichon, A.; Westwood, J.T.; Sokolowski, M.B. (Behavior Genetics, 2005)
Genetic variation in the gene foraging (for) is associated with a natural behavioral dimorphism in the fruit fly, Drosophila melanogaster. Some larvae, called 'rovers', have increased foraging locomotion compared to others, called 'sitters', and this difference is directly related to for-encoded cGMP-dependent protein kinase (PKG) activity. Here we report that larvae with mutations in the gene dgcalpha1, which encodes a soluble guanylyl cyclase (sGC) subunit, have increases in both PKG activity and foraging locomotion. This is contrary to our original prediction that, based on the role of sGC in the synthesis of cGMP, dgcalpha1 mutant larvae would have deficient cGMP production leading to decreased PKG activation and thus reduced larval foraging locomotion. We performed DNA microarray analyses to compare transcriptional changes induced by a dgcalpha1 mutation in both rover and sitter wildtype genetic backgrounds. In either background, we identified many genes that are differentially transcribed, and interestingly, relatively few are affected in both backgrounds. Furthermore, several of these commonly affected genes are enhanced or suppressed in a background-dependent manner. Thus, genetic background has a critical influence on the molecular effects of this mutation. These findings will support future investigations of Drosophila foraging behavior.